O enredo assistencial de uma organização de atleta evangélico : a fundação Edmilson na cidade paulista de Taquaritinga - Batista, Breno Minelli (Universidade Federal de São Carlos, 2017)
The care work comprises a very heterogeneous field of the third sector. The constitution and motivation to carry out this activity is linked by many authors to religious aspects, throughout history. However, the scope of religion in the segment of non-governmental institutions that practice care activities is quite broad and still unknown in certain aspects. Considering this context, the research that generated this dissertation had as its objective the study of the political-assistance plot of the Edmilson Foundation located in Taquaritinga-SP, founded and led by a former soccer player who worked abroad and was a five-time world champion: José Edmilson Gomes de Moraes. The investigative work involved: bibliographical review; Information gathering on social networks, newspapers and news portals; And semi-structured interviews with members of the foundation. It sought to evaluate how the aspects arising from other social fields and components of the care work present in this organization, led by an evangelical athlete with an international reputation, were developed.
Keywords: Trabalho assistencial; Terceiro setor; Pentecostalismo; Atletas evangélicos; Fundação Edmilson; Care work; Third sector; Pentecostalism; Evangelical athletes; Edmilson foundation; CIENCIAS HUMANAS::SOCIOLOGIA